Study of adsorption cooling cycle for automobile air conditioning - Prawira, Raditya Yudha (2014)
The uprising of global warming urges us to replace current air conditioning system as it poses hazard to the environment. Adsorption cooling cycle is one promising alternative solution as it is far more environmental friendly and can be powered by low-grade heat.